Randomised clinical trial: safety, pharmacokinetics and pharmacodynamics of trazpiroben (TAK‐906), a dopamine D2/D3 receptor antagonist, in patients with gastroparesis. Issue 3 (20th June 2021) - Kuo, Braden; Scimia, Cecilia; Dukes, George; Zhang, Wenwen; Gupta, Saurabh; Chen, Chunlin; Chuang, Emil; Camilleri, Michael
Summary: Background: Gastroparesis is a chronic gastric motility disorder. Dopamine D2 /D3 receptor antagonists metoclopramide and domperidone are current treatment options but are associated with central nervous system and cardiovascular safety concerns, respectively, precluding chronic use. Trazpiroben (TAK‐906), a dopamine D2 /D3 receptor antagonist, is under development for chronic treatment of moderate‐to‐severe gastroparesis. Nonclinical data suggest trazpiroben will have D2 /D3 receptor antagonism comparable with metoclopramide or domperidone. Aims: To evaluate the safety, tolerability, pharmacokinetics and pharmacodynamics (effect on prolactin and gastric function) of twice‐daily trazpiroben (5, 25 and 100 mg) in participants with gastroparesis. Methods: This phase 2a pilot study evaluated gastric emptying using the gastric emptying breath test, with metoclopramide as an internal control. Gastric accommodation and gastroparesis symptoms were assessed using the nutrient drink test and American Neurogastroenterology and Motility Society Gastroparesis Cardinal Symptom Index‐Daily Diary, respectively. Results: Overall, 51 participants were enrolled. Trazpiroben was well tolerated, demonstrating a favourable safety profile without cardiovascular or central nervous system adverse events. All trazpiroben doses were rapidly absorbed and eliminated (t1/2z 4‐5 hours), and D2 /D3 receptor target engagement confirmed by increased serum prolactin (peaking at trazpiroben 25 mg). No effect on gastric emptying was demonstrated with trazpiroben or metoclopramide ( P  > 0.05), although benefits in volume‐to‐fullness were seen at trazpiroben 5 mg ( P  > 0.05) and 25 mg (88.5 vs −26.3 mL; P  = 0.019), and nonsignificant numerical aggregate symptom score improvements were observed with trazpiroben 25 mg vs placebo ( P  = 0.182). Conclusions: Trazpiroben was well tolerated with a favourable safety profile, supporting its further development for the treatment of gastroparesis. ClinicalTrials.gov identifier: NCT03268941. Abstract : Safety, pharmacokinetics and pharmacodynamics of trazpiroben(TAK‐906), a dopamine D2/D3 receptor antagonist, inpatients with gastroparesis.